Polarimetric imaging method for target enhancement in haze based on polarimetric retrieval. Issue 11 (25th June 2019) - Zhang, Wenfei; Liang, Jian; Xing, Fei; Man, Zhongsheng; Ge, Xiaolu; Fu, Shenggui
ABSTRACT: Polarimetric imaging has been proven to be an effective way in detecting the targets of interest in complicated surroundings by analyzing the polarization property, instead of the intensity, of the light emanating from the objects. Unfortunately, polarimetric imaging encounters difficulty when the surroundings are very scattered, where on the one hand the polarization property of the object light usually becomes very faint after a strong depolarized scattering process; on the other hand, the object light will be blended with the atmospheric light scattered by haze particles (airlight). In this paper, we propose a polarimetric imaging retrieval method that can be used for such challenging conditions. Firstly, the airlight radiance is estimated precisely. Then, the airlight is removed from the hazy images. Finally, the residual polarization property of the object light is regained, which ensures the validity of the polarimetric imaging method in these conditions. The experiments confirm that the proposed method is useful in enhancing polarimetric imaging detection in haze.